Design and testing of fiber bragg grating (FBG) ultrasound sensor - Lee, Wei Chun. (2009)
Fiber Bragg grating (FBG) is a type of distributed Bragg reflector created from a small section of optical fiber that reflect a certain wavelength of light and transmit others. This is achieved by including a periodic variation to the reflective index of the fiber core which would then generate a wavelength specific dielectric mirror. FBG ultrasound sensors have been potential alternative for ultrasound detection because of their unique advantages over piezoelectric sensors, such as immunity towards electromagnetic interference, small in size, light weight and stability. Till date, all Fiber Bragg grating ultrasound sensors are based on elasto-optic effect and geometrical distortion interaction between ultrasound and Fiber Bragg grating. This project proposed on designing and the construction of a circuit used to amplify the two side lobes on the both sides of the Bragg wavelength. The amplification gain that would be required from the circuit would be between thirty to fifty times of the original signal. The circuit is also required to be able to accurately amplify the signal with minimum interference from noise produce by the circuit when it operates at a high frequency range between 3MHz to 10MHz. The circuit is designed as a two stage amplification circuit whereby the first stage converts the current to voltage and amplifies the gain and the second stage will then further amplify the gain from the previous stage. The amplification circuit would also consist of a photodetector which would be connected at the front of it. The photodetector would be used to receive the signal from the source. Similarly designed circuits have been studied and compared with the proposed amplification circuit.